2016
DOI: 10.1002/ctpp.201600013
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic Fluid Accelerator under High‐Speed Free Air Stream

Abstract: The electrostatic fluid accelerator (EFA) generates ionic wind with a simple structure that barely obstructs the free air stream or produce excessive noise. This paper presents the velocity characteristics of an EFA under a high speed free air stream to simulate an EFA-powered propulsor. The results show that when the EFA generates identical velocity to the free air stream, the EFA contributes 25% of the resultant velocity. When the EFA is replaced by a rotary fan that generates identical velocity to the free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…Both studies reported that the ionic wind provides the largest amount of improvement when the bulk flow is at a low Reynolds number, where the inertia of the bulk flow does not overwhelm the secondary flow produced by the ionic wind. These findings are not unique to thermal applications, as EHD pumps lose effectiveness as secondary wind devices as the velocity of the bulk flow increases [130]. This can be understood from the scaling arguments described in section 2.3, where it is necessary for  Re E HD 2 for the EHD body force to overcome the inertia of the bulk flow.…”
Section: Ehd For Cooling and Thermal Managementmentioning
confidence: 99%
“…Both studies reported that the ionic wind provides the largest amount of improvement when the bulk flow is at a low Reynolds number, where the inertia of the bulk flow does not overwhelm the secondary flow produced by the ionic wind. These findings are not unique to thermal applications, as EHD pumps lose effectiveness as secondary wind devices as the velocity of the bulk flow increases [130]. This can be understood from the scaling arguments described in section 2.3, where it is necessary for  Re E HD 2 for the EHD body force to overcome the inertia of the bulk flow.…”
Section: Ehd For Cooling and Thermal Managementmentioning
confidence: 99%
“…Air molecules will be charged when passing around the ionization region. The charged air molecules will then move to the collector electrode following the electric field, transferring charges and momentum to other air molecules [ 10 ]. The bulk air movement is the result, also known as ionic wind or EHD flow [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%